Epidural Hematoma With Coma - Richard Stair (Association of American Medical Colleges, 2007)
Abstract This resource is a simulation case concerning a patient who has sustained a head injury as a result of a fall and presents with coma. The simulation requires knowledge and application of Advanced Trauma Life Support principles for successful management. Also, this case needs to be run in a time-sensitive manner in order to convey the genuine urgency of the injury. Finally, although it can be difficult to encourage utilization of consultants in simulation experiences, this is a required element of the case. The case file contains three elements that help in running the simulation: (1) A case narrative acts as a blueprint for the teacher of what to say and what actions should be taken from start to finish in the case. (2) Lab data sheets include the laboratory studies for the simulated patient. (3) Simulator preparation sheets are used to develop how the simulator should respond as the student progresses through the case. These preparation sheets start with the settings, including vital signs and physical findings, that the simulator should present at the beginning of the case. Next come the timing and steps that need to be followed to trigger how the simulator responds. If the student performs the given set of actions, the simulator can be triggered to respond to the proper intervention. If the actions are not taken or take too long, the simulator can be triggered to worsen. Both pathways are included in the resource. Along with these three elements, supporting images are provided. This simulation experience enables faculty to assess the ability of residents and students to perform a trauma history and physical, make management decisions, and perform critical interventions in a patient with a head injury.